Profiling green consumers through culture, beliefs and demographics: an Indian study. (30th July 2019) - Sreen, Naman; Sadarangani, Pradip H.; Gogoi, Bidyut Jyoti
Consumers today not only view companies as profit centres, but also as institutions that should be sensitive to social problems such as environmental degradation. As a result, organisations have started considering the environmental needs of consumers by focusing on 'sustainability as a business goal'. Green products may help companies to improve their bottom line and brand image. This paper forms green consumer segments on the basis of cultural values, psychographics, and demographics. Demographics include income, gender and education. Cultural values include collectivism and long-term orientation (LTO) from Hofstede and man-nature orientation (MNO) from a value orientation model by Kluckhohn and Strodtbeck (1961). Psychographics are derived from theory of planned behaviour (TPB). The results indicate that there are four distinct segments. Two of these segments 'female green activists' and 'green outlook male activists' are identified as the groups that are more willing to buy green products. Finally, implications from the results are derived for practitioners and policy-makers to develop targeting strategies for these segments.